2018
DOI: 10.1021/acsnano.8b02739
|View full text |Cite
|
Sign up to set email alerts
|

Doping-Free Complementary Logic Gates Enabled by Two-Dimensional Polarity-Controllable Transistors

Abstract: Atomically thin two-dimensional (2D) materials belonging to transition metal dichalcogenides, due to their physical and electrical properties, are an exceptional vector for the exploration of next-generation semiconductor devices. Among them, due to the possibility of ambipolar conduction, tungsten diselenide (WSe) provides a platform for the efficient implementation of polarity-controllable transistors. These transistors use an additional gate, named polarity gate, that, due to the electrostatic doping of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 57 publications
0
91
0
Order By: Relevance
“…In regard to tungsten dichalcogenides, WSe 2 is the most proverbially studied material for building CMOS inverters by reasons of its inherent ambipolar characteristic, wide energy gap of 1–2 eV and ultrathin thickness of <1 nm . Besides, FETs based on WSe 2 display large charge carrier mobilities of more than 100 cm 2 V −1 s −1 , on/off ratio of exceeding 10 6 and relatively small subthreshold swing of 60 mV decade −1 due to the ultrathin semiconducting channel and hence better electrostatic modulation, which provides lots of advantages to fabricate low‐power logic inverters with extremely low off‐state voltage and large gain value . Recently, Pu et al demonstrated high‐performance CMOS inverters on the basis of CVD‐grown WSe 2 monolayers and ion gel dielectric (Figure d) .…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…In regard to tungsten dichalcogenides, WSe 2 is the most proverbially studied material for building CMOS inverters by reasons of its inherent ambipolar characteristic, wide energy gap of 1–2 eV and ultrathin thickness of <1 nm . Besides, FETs based on WSe 2 display large charge carrier mobilities of more than 100 cm 2 V −1 s −1 , on/off ratio of exceeding 10 6 and relatively small subthreshold swing of 60 mV decade −1 due to the ultrathin semiconducting channel and hence better electrostatic modulation, which provides lots of advantages to fabricate low‐power logic inverters with extremely low off‐state voltage and large gain value . Recently, Pu et al demonstrated high‐performance CMOS inverters on the basis of CVD‐grown WSe 2 monolayers and ion gel dielectric (Figure d) .…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…Open base BJT is a commonly available photodetector. The advantages of making heterostructures and electrostatic doping in TMDCs allow for novel BJT architectures for improved photodetection responsivity [99][100][101][102][103][104][105][106]. Figure 5(b) (i, ii) illustrate the schematic of the 2D heterostructure BJT consisting of three materials (WSe 2 /black phosphorus/MoS 2 ) and its band diagram under illumination showing the amplification mechanism, respectively.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Considerable efforts have been devoted to realize 2D CMOS functions in the past few years [10][11][12][13] . Early attempts focused on using two different 2D semiconductors, where one material is used for the NMOS (e.g., MoS 2 and MoSe 2 ) and a different material is used for PMOS (e.g., black phosphorus, WSe 2 ) [14][15][16] .…”
mentioning
confidence: 99%